Desain Perangkat Pengurai Sampah Organik dengan Teknik Vermicomposting - Hari Nugraha; Komang Subadri; Jasmine Reyna Maharani; Praditya Arzaqi Anantyo; Dhika Galang Adi Hanggoro; Keisha Zalikha (Jurnal Desain Produk Nasional, 2026)
This study aims to develop an innovative solution for managing organic waste, particularly discarded fruit residues, through the application of vermicomposting (composting using earthworms). The research is motivated by the growing volume of organic waste generated in society, especially from commercial activities such as juice vendors, which necessitates effective strategies for organic waste management. This research focuses on the design, fabrication, and testing of a prototype device for converting organic waste into compost. The device is engineered to efficiently facilitate the decomposition of fruit waste through vermicomposting, incorporating considerations of ergonomics, time efficiency, and ease of maintenance. The research methodology comprises five key stages: problem identification, solution design, prototype development, product testing, and result evaluation. The findings demonstrate that the developed device is highly effective in transforming organic waste into environmentally friendly compost. The primary contribution of this research lies in the development of an innovative device that supports the utilization of fruit waste as a sustainable resource while offering practical solutions for communities to manage organic waste. This study introduces novelty through the integration of simple yet effective technology to promote environmental sustainability.